2015
DOI: 10.1007/s10815-015-0441-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood type predicts live birth in the infertile population

Abstract: Purpose To determine if blood type in infertile women relates to the likelihood for live birth (LB) following IVF, and to the etiology for infertility. Methods Retrospective study of patients undergoing IVF at two academic centers in the northeast US. Relationships between blood type (A, B, AB, O) and patient characteristics, IVF cycle parameters and LB were assessed utilizing multivariable logistic regression analyses. Results In the studied population (n=626), women with type O were significantly more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Similar findings were found in women with idiopathic infertility with wide confidence intervals around the point estimates. When pooling current data with those from previous retrospective series [23,24], the summary estimate showed no significant effect of non-O blood group on the risk of live birth (OR 1.03; 95% CI, 0.90 to 1.19), with no between study heterogeneity (Fig. 1).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Similar findings were found in women with idiopathic infertility with wide confidence intervals around the point estimates. When pooling current data with those from previous retrospective series [23,24], the summary estimate showed no significant effect of non-O blood group on the risk of live birth (OR 1.03; 95% CI, 0.90 to 1.19), with no between study heterogeneity (Fig. 1).…”
Section: Resultsmentioning
confidence: 85%
“…As hypothesized for other inherited thrombophilia, non-O blood type could increase the risk of thrombosis of the vessels at the maternal-fetal interface with potential negative consequences for implantation or development of the placenta. Two recent retrospective studies evaluated the effect of ABO blood type on live birth in women undergoing IVF [23,24]. In a series of 626 women at their first or repeated IVF attempt, Goldsammler and colleagues suggested that blood type B was associated with an increased likelihood of live birth [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study has observed the relationship between blood group and IVF-ET pregnancy outcomes and found that blood group B is associated with increased live birth rate [ 7 ]. However, subsequent studies have confirmed that ABO blood group is not related to the IVF pregnancy outcome [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%